Research on Dynamic Evolution of Systemic Risk in Chinese Banking System - Fan, Hong; Sheng, Wanqin (Frontiers in Physics, 2020)
Systemic risk is not only related to the contagious risk of interbank market risk exposure, but also to the credit risk exposure. At the same time, the dynamic characteristics of banking system also affect the systemic risk. A large number of studies have revealed the contagious risk of interbank market risk exposure, but the systematic risk research that considers these factors at the same time is still rare. Therefore, the present paper constructs dynamically evolving banking systemic risk assessment model under double risk exposures in the same framework that includes two parts: one is the assessment of credit risk; the other is the contagious risk. On the assessment of credit risk, we use Geometric Brownian Motion in physics and Monte Carlo simulation calculation method based on the big data of the stock market. On the assessment of contagious risk, we use the method of Geometric Brownian Motion in physics and minimum density method. Then we use data of 205 Banks and 3,017 listed companies in 18 industries in Chinese to study the dynamic evolution law of the Chinese banking systemic risk. The results show that the evolution characteristics of credit risk of 18 real industries can be divided into 4 types which are stability after decline, increase in fluctuation, decrease in fluctuation, and fluctuation. The systemic risk of Chinese banking system with the double risk exposures gradually increased with the evolution of time, and then stabilized at a certain degree. Among them, the initial increase of contagious risk is fast, and then stable; the credit risk starts small, slowly increases, and eventually stabilizes. The evolution degree of contagious risk is higher than that of credit risk. Large banks have the strongest ability to withstand the impact of double risk exposures, while foreign banks have the weakest.